BTEC National Engineering - Tooley, Michael H.; Dingle, Lloyd (Oxford : Newnes, 2002)
Meeting the needs of those studying for the BTEC national engineering, this student textbook presents the compulsory core material in a manner that encourages the reader to explore engineering for herself or himself.
Includes index.
Keywords: Engineering; Engineering -- Problems, exercises, etc; Technology